Potential Distribution and Connectivity for Two Plethodontid Salamanders: Conservation Areas and Landscape Corridors for Two Endemic Species of México and Guatemala. - Bolom-Huet, René; Pacheco, Xareni P.; Muñoz-Alonso, Antonio; Sunny, Armando (Environmental Management, 2022)
Habitat loss is one of the most important threats to biodiversity; it alters the habitat connectivity of species and is among the main causes of the global amphibian extinction crisis. Identifying the potential areas of distribution and connectivity of species is of the utmost importance so that informed decisions can be made for the conservation of vulnerable amphibian populations. In this study, we performed species distribution models and used circuit theory to model omnidirectional connectivity for two plethodontid salamanders of conservation concern distributed in the forests of Chiapas, Mexico, and Guatemala (Bolitoglossa franklini and Bolitoglossa lincolni). Potential distribution maps show an affinity for well-preserved montane forests for both species. Likewise, we found that the niches of the species are not similar. The connectivity models show that the main areas of connectivity are in the Meseta Central de Chiapas, Sierra Madre de Chiapas, and the Cordillera Volcánica Guatemalense, in this last range, important areas of connectivity were located, as well as least-cost paths and barriers to the movement of both species. We identified that important areas of climatic suitability and connectivity are not within the protected natural areas and may be threatened by the increasing influence of anthropogenic activities. The results of our study show the importance of preserving the regional forests to ensure the persistence of species with arboreal habits and high sensitivity to habitat transformation, as well as to recognize and prioritize potential areas for management and protection in both southern Mexico and Guatemala.